2020
DOI: 10.21873/anticanres.14401
|View full text |Cite
|
Sign up to set email alerts
|

Low Eosinophil Percentages as a New Predictive Marker for Infusion Reactions Due to Trastuzumab

Abstract: Background/Aim: Infusion reactions (IRs) often occur with trastuzumab. Although premedication by nonsteroidal anti-inflammatory drugs can be effective to a certain extent, IRs are still common and infrequently severe. Therefore, a predictive marker that can select patients requiring further prophylaxis is useful for appropriate prevention, but remains unclear. Patients and Methods: We conducted a retrospective analysis for 136 consecutive female inpatients aged 18 years and older who received 8 mg/kg of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Therefore, the increased dose of rituximab may help explain the high incidence of IRRs. In previous studies on other monoclonal antibodies, including trastuzumab 15,17) and ocrelizumab, 18) high actual BMI has been reported to be a predictive marker associated with IRRs.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the increased dose of rituximab may help explain the high incidence of IRRs. In previous studies on other monoclonal antibodies, including trastuzumab 15,17) and ocrelizumab, 18) high actual BMI has been reported to be a predictive marker associated with IRRs.…”
Section: Discussionmentioning
confidence: 92%
“…In a recently published retrospective study, no association between survival and eosinophil count was detected in 601 breast cancer patients of all subtypes [ 74 ]. Takahashi et al showed an association between infusion reactions to trastuzumab and a low eosinophil count, while another study showed an association between a high level of immunoglobulin E and a lower risk of cardiotoxicity in patients treated with anthracyclines and trastuzumab, suggesting that eosinophils are also involved in tolerance to anticancer treatments [ 75 , 76 ].…”
Section: Eosinophils and Breast Cancermentioning
confidence: 99%
“…In a previous study, low eosinophil levels were associated with trastuzumab-induced IRR in breast cancer patients. 53 High eosinophil counts were a risk factor for cetuximab-induced IRR in patients with squamous cell carcinoma of the head and neck. 42 Therefore, the influence of blood eosinophils on the development of IRRs caused by monoclonal antibody preparations shows conflicting results.…”
Section: Discussionmentioning
confidence: 93%